2020
DOI: 10.1038/s41598-020-69968-y
|View full text |Cite|
|
Sign up to set email alerts
|

Increased persistence of avoidance behaviour and social deficits with L.rhamnosus JB-1 or selective serotonin reuptake inhibitor treatment following social defeat

Abstract: Chronic social defeat (CSD) in mice has been suggested as a model for studying post-traumatic stress disorder (PTSD). Our previous work indicated that exposure to Lactobacillus rhamnosus JB-1 (JB-1) during CSD can attenuate subsequent behavioural and immune disruption, suggesting a potential for microbe based therapeutic approaches in PTSD. In the current study, we assessed the ability of JB-1 to mitigate the behavioral consequences of CSD when treatment is instigated in the early post-stress period and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Probiotic food supplementation can reduce stress-induced GI symptoms in volunteers [30], decrease depression scores, alter brain activity in patients with IBS [31], and improve symptoms associated with ASD and PD [8]. These probiotics that affect CNS-related functions and behaviors are classified as psychobiotics, including L. plantarum PS128, Bifidobacterium longum 1714 [32], B. longum NCC3001 [31], Lactobacillus rhamnosus JB-1 [33], Lactobacillus helveticus R0052, and B. longum R0175 [30]. Although these psychobiotics have been suggested to regulate CNS-related functions through the gut-brain axis, their regulation in the intestine remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic food supplementation can reduce stress-induced GI symptoms in volunteers [30], decrease depression scores, alter brain activity in patients with IBS [31], and improve symptoms associated with ASD and PD [8]. These probiotics that affect CNS-related functions and behaviors are classified as psychobiotics, including L. plantarum PS128, Bifidobacterium longum 1714 [32], B. longum NCC3001 [31], Lactobacillus rhamnosus JB-1 [33], Lactobacillus helveticus R0052, and B. longum R0175 [30]. Although these psychobiotics have been suggested to regulate CNS-related functions through the gut-brain axis, their regulation in the intestine remains largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this bacterial genus has been repeatedly implicated in enhanced fear memory retention in mammals. [ 37–39 ] Lactobacillus rhamnosus JB‐1 , for example, has been associated with both aggressor avoidance behaviors as well as enhanced fear memory recall in mice. [ 37,38 ] These phenotypic changes in mice were accompanied by gene expression profiles in the brain related to fear memory, impaired fear extinction, and stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37,38 ] These phenotypic changes in mice were accompanied by gene expression profiles in the brain related to fear memory, impaired fear extinction, and stress responses. [ 37,38 ]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, related studies have indicated that probiotic use reduced depressive symptoms and improved the functionality of both the HPA axis and was equivalent to treatment with the antidepressant Citalopram in murine studies ( 106 , 146 , 152 ). However, as with any emerging therapeutic option, some failed to achieve the desired effect, a result that has been reported in a number of studies ( 153 155 ).…”
Section: Probiotics and Depressionmentioning
confidence: 98%